"Bean's World": (Mine) Crafting affective atmospheres of gameplay, learning, and care in a children's hospital. (December 2015) - Hollett, Ty; Ehret, Christian
This article contributes to research on the felt-experience of new media. It describes how the body's corporal capacities are augmented through one 12-year-old boy's play of the video game, Minecraft, while hospitalized. Expanding player-centric perspectives of video gameplay, the authors leverage work on place-events to develop an intra-actional methodology aligned with their relational materialist analysis. Their analysis illuminates how multiple human and nonhuman bodies become entangled in gameplace-events and potentially generate affective atmospheres. Analysis shows how these atmospheres reverberate and adhere within social space, revealing experiences of new media as less a one-to-one transaction between player and game and more an affective experience felt across multiple bodies and temporalities. Implications, suggesting both how intimate atmospheres developed during gameplay and how those atmospheres (re)shaped care in the hospital, point toward new media's potential to engage users in uniquely meaningful felt-experiences made visible—and felt—through methods of intra-action and relational materialism.